The impact of the global financial crisis on public expenditures on education and health in the economies of the former Soviet Union - Alexander Chubrik; Marek Dabrowski; Roman Mogilevsky; Irina Sinitsina (Center for Social and Economic Research (CASE), 2011)
This paper provides an overview of public expenditures on education and healthcare in Belarus, Georgia, Kyrgyzstan, Moldova, Russia, Ukraine and some other countries of the former Soviet Union before and during the global financial crisis. Before the crisis, the governments of these countries were substantially increasing spending on education and health. The crisis adversely affected the FSU countries and worsened their fiscal situation. The analysis indicates that during the crisis, despite the fiscal constraints, public education and health expenditures have mostly been maintained or increased in almost all of these countries. However, the crisis situation was not taken as an opportunity to address these countries' key education and healthcare problems related to demographic changes, insufficient per capita expenditure levels, the low efficiency of public spending and the insufficient quality of services. These issues form an ambitious reform agenda for these countries in the medium- and long-term.
Keywords: E62; H50; H51; H52; I18; I22; 330; Fiscal policy; Former Soviet Union; Education financing; Health financing; Global economic crisis; Öffentliche Finanzen; Öffentliche Ausgaben; Finanzpolitik; Bildungswesen; Bildungsfinanzierung; Bildungsreform; Gesundheitswesen; Gesundheitskosten; Finanzkrise; GUS-Staaten